The Shift of Soil Bacterial Community After Afforestation Influence Soil Organic Carbon and Aggregate Stability in Karst Region - Lan, Jiacheng; Wang, Shasha; Wang, Junxian; Qi, Xue; Long, Qixia; Huang, Mingzhi (Frontiers in Microbiology, 2022)
Soil microbes regulate the carbon cycle and affect the formation and stabilization of soil aggregates. However, the interactions between the soil microbial community and soil organic carbon (SOC) fractions, orgnic carbon (OC) content in aggregates, and soil aggregate stability after afforestation are rarely studied and remain poorly understood. In our study we investigated SOC fractions in bulk soil, aggregate-associated OC content, soil aggregate stability, and soil bacterial community with high-throughput 16S rRNA sequencing at sites representing natural secondary forest (NF) and managed forest (MF), with cropland (CL) as reference in a degraded karst region of Southwest China. Our results showed that afforestation remarkably increased the SOC fraction and OC content in aggregates, the mean weight diameter (MWD), and the mean geometric diameter (GMD). The most dominant bacterial phyla detected were Acidobacteriota, Actinobacteriota, Proteobacteria, and Chloroflexi across all soils. Afforestation remarkably altered the relative abundances of most of the dominant soil bacteria at the phylum, class, and order levels. Interestingly, such changes in the abundance of soil bacteria taxa were significantly correlated with SOC fraction, aggregate-associated OC content, MWD, and MGD. The abundance of dominant bacterial taxa such as Methylomirabilota, Latescibacterota, Methylomirabilia, MB-A2-108, norank_Latescibacterota; Dehalococcoidia, Rokubacteriales, Gaiellales, Microtrichales, norank_c__MB-A2-108, norank_c__norank_p__Latescibacterota, Rhizobiales, and S085 not only remarkably increased but also showed significant and positive correlation with SOC fractions and aggregate-associated OC content after afforestation. Moreover, the relative abuandance of Methylomirabilota, Methylomirabilia, Rokubacteriales, Latescibacterota, and Rhizobiales was positively correlated with MWD and MGD. Results indicated the importance of certain soil bacteria for regulating SOC storage and soil aggregate stability. We concluded that afforestation on cropland could alter the abundance of soil bacteria, and these changes modulate the stability of soil aggregates and SOC fractions.